Hubungan Usia Ibu Menyusui Dengan Pemberian Asi Ekslusif - Sari, Atika Kurnia; Fitriani, Rani (MIDWIFERY JOURNAL, 2022)
Background : In 2020 WHO again presented data in the form of the number of exclusive bresst feeding globally, althought there has been an increase, this figure did increase significantly, namely arround 44% of infant agged 0-6 monthh worldwide who received exlusive breastfeeding during the 2015-2020 period. Of the 50% target of exlusive breastfeeding will have an impact in the quality and vitality of the next generation, globally  in 2019, 144 million children under five are estimated to the stunterd, 47 million are sstimated to the underweight and 38,3 million are overweight or obese (WHO, 2020).Purpose :  Knowing Relationshiop Age Of A Breastfeeding Mother With Exlusive Breast Milk At Semuli Raya Posyandu Anf Suka Maju The Work Area Semuli Raya Puskesmas, Abung Semuli Kabupaten Lampung Utara Tear 2020Methode : This study uses quantitative analytical research methods. The measurement method used is by interview and measuring instrument is a questionaire. The population in the study were 105 babies aged 0-6 months who were given exlusive breastfeeding and sample in this study were 35 breastfeeding mother at the Semuli Raya osyandu and Suka Maju Work Area at the Semuli Raya health center, Abung Semuli District, North Lampung Regency in 2022. The sampling technique used ws accidental sampling technique or sample taken from respondent or cases that happen to exist  in a certain place or condition that meets the criteria.Result : The result of the research that has been concucted on the relationship between material age and exclusive breastfeeding in the posyandu Semuli Raya and Suka Maju, the working area of the Puskesmas Abung Semuli Sub-district, North Lampung district in the 2022, it can be concluded that 43% of infant given exclusive breastfeeding and those who were not given exclusive breastfeeding. Exclusive breastfeeding as much as 57%.Conclusion : The conclusion of the result shows that based on statistical test using chi square based on the age of breastfeeding mother with exclusive breastfeeding. The X2count value is 7.176 > X2 table 5.991 because Ho is rejected in Ha is accepted. This means that there is a relationship between maternal age and exclusive breastfeeding at the semuli raya Posyandu and Suka Maju Working Area of the Semuli Raya Helath Center, Abung Semuli District, North Lamung Regency in 2022.Suggestion Midwives can work together with cadres in providing health education using demonstration methods so that breastfeeding mothers of various ages can apply exclusive breastfeeding to their babies Keyword : Age of breastfeedingmother with eclusive breastfeeding ABSTRAK Latar Belakang : Pada tahun 2020 WHO kembali memaparkan data berupa angka pemberian ASI Ekslusif secara global, walaupun telah ada peningkatan namun angka ini tidak meningkat cukup signifikan yaitu sekitar 44% bayi usia 0-6 bulan diseluruh dunia yang mendapatkan ASI Ekslusif menurut WHO. Masih rendahnya pemberian ASI Ekslusif akan berdampak pada kualitas dan daya tahan hidup generasi penerus, secara global pada tahun 2019, 144 juta balita diperkirakan stunting, 47 juta diperkirakan kurus dan 38,3 juta mengalami kelebihan berat badan atau obesitas (WHO, 2020).Tujuan : Mengetahui Hubungan Usia Ibu Menyusui Dengan Pemberian Asi Ekslusif Di Posyandu Semuli Raya Dan Suka Maju Wilayah Kerja Puskesmas Semuli Raya Kecamatan Abung Semuli Raya Kabupaten Lampung Utara Tahun 2020.Metode : penelitian ini menggunakan metode penelitian analitik kuantitatif cara ukur yang di gunakan adalah dengan wawancara dan alat ukurnya kuesioner. Populasi dalam penelitian ini adalah sebanyak 105 bayi usia 0-6 bulan yang diberikan ASI Ekslusif, dan usia 6-24 bulan sebanyak 106 bayi yang diberikan ASI Ekslusif, dan sampel dalam penelitian ini terdapat 35 Ibu yang menyusui di Posyandu Semuli Raya dan Suka Maju wilayah kerja di Puskesmas Semuli Raya Kecamatan Abung Semuli Kabupaten Lampung Utara tahun 2022. Teknik sampling yang digunakan adalah teknik sampling aksidental (accidental) atau sampel yang diambil dari responden atau kasus yang kebetulan ada disuatu tempat atau keadaan tertentu yang sesuai dengan kriteria.Hasil : hasil penelitian yang telah dilakukan tentang hubungan usia ibu menyusui dengan pemberian Asi Ekslusif di posyandu Semuli Raya dan Suka Maju wilayah kerja Puskemas kecamatan Abung Semuli Raya Kabupaten Lampung Utara tahun 2022.Kesimpulan bahwa bayi yang diberikan Asi Ekslusif sebanyak 43% dan yang tidak diberikan Asi Ekslusif sebanyak 57%.Saran Bidan dapat bekerjasama dengan kader dalam memberikan penyuluhan kesehatan dengan metode demonstrasi agar ibu menyusui dengan berbagai usia dapat lebih menagaplikasikan menyusui bayi nya secara eksklusif Kata Kunci : Usia Ibu Menyusui dengan Pemberian Asi Ekslusif